Networks of social capital family in the east región of Jujuy (Argentina) during the first three decades of the 20th century - Fernández, Federico (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2018)
In this research analyzes the utilization of the social capital category, and its possible linkages with the processes of accumulation relational and spatial mobility between extended family with multiple residences within the eastern region of the province of Jujuy. The main source of information with which it has developed work, comes from a set of baptismal records made between 1902 and 1935 by priests of the Prelature of Humahuaca, Jujuy, on the population living in the region known as Valle Grande. The results obtained after the ordering and the analysis of social networks (ARS) data entered in the baptismal records, give account of a series of relational feasible to be described under the category of family social capital.